(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The results of investigation of optical absorption and photoluminescence (PL) of topaz, beryl and yttrium aluminium garnet crystals doped with different concentrations of transition ions exposed to fast neutron irradiation and electron irradiation are presented. We suppose that irradiation leads to the formation of two types of complex centers: "Me2+-F+ (or F) centre" and complex centers, which consist of a cation vacancy and an impurity (iron, manganese and chromium) ion. Exchange interaction between radiation defects and impurity ions during neutron or electron irradiation gives rise to appearance of additional absorption and luminescence band broadening in investigated crystals.